INFLUENCIA DE LAS DROGAS EN LA COMUNICACIÓN INTRAFAMILIAR EN LOS HABITANTES DEL SECTOR PLAYA GRANDE - Andrade Rodriguez, Gary Gabriel (2022)
The present investigative work arises from the need to know the influence that drugs have on the intra-family communication of the citizens of the Playa Grande sector. To achieve the stated objective, a survey was prepared and executed, which contained a total of 10 questions addressed to young citizens of the sector to be later analyzed, interpreted and tabulated and to be able to provide a solution. For the solution of the existing problem, it is proposed to write techniques that help intra-family communication and the issue of drugs because it is an issue that citizens deal with from an early age.